THE EFFECT OF MICROWAVE HEATING AND Li1.3Al0.3Ti1.7(PO4)3 COATING ON STABILITY AND BATTERY PERFORMANCE OF LiNi0.8Co0.15Al0.05O2 CATHODE MATERIAL - Hendra Widyadharma, Putu
LiNi0.8Co0.15Al0.05O2 (LNCA) is a promising material with good performance which is used as cathode battery material. It has a high specific capacity, high electronic and ionic conductivity, easy to synthesis, and good stability that make the material applicable to the comercial aplication such as electric vehicle. Since the material has a long-term synthesis and low stability under the high temperature, to overcome the problem, We reported an improvement of stability and electrochemical performace by performing surface coating using Li1.3Al0.3Ti1.7(PO4)3 (LATP). Beside that we developed a new synthesis method by involving microwave heating treatment to reduce the synthesis time and improve efficiency. Synthesis for both coating LATP and microwave heating was carried out via wet chemical precipitation method. The LNCA powder was characterized by using X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM) to investigate the structure and surface morphology of the Sample. Furthermore, we used Electrochemical Impedance Spectroscopy (EIS) and Charging-discharging test to characterized electrochemical and stability of the material. Based on XRD and SEM characterization result, LiNi0.8Co0.15Al0.05O2 (LNCA) material has been successfully synthesized which has layered hexagonal structure. EIS characterization on LATP-coated LNCA resulting in lower charge transfer resistance value to 60,01 ?. Furthermore, the ionic conductivity of coated material has also increased to 1,94 × 10-10 cm2s-1. Synthesis of the material involving microwave heating treatment provides a faster synthesis time of up to 6 hours with better crystal structure parameters. Specific capacity of microwave-assisted cathode material also show better value, 81,3 mAh g-1 with 86,4% capacity retention, compared to cathode with standart synthesis method that has 77,4 mAh g-1 spesific capacity with 69,2% capacity retention.